Insights into the stereoisomerism of dihydroquercetin: analytical and pharmacological aspects - Terekhov, Roman P.; Savina, Anastasiya D.; Pankov, Denis I.; Korochkina, Maria D.; Taldaev, Amir; Yakubovich, Liubov M.; Zavadskiy, Sergey P.; Zhevlakova, Anastasiya K.; Selivanova, Irina A. (Frontiers in Chemistry, 2024)
Dihydroquercetin (DHQ) is a representative of flavonoids that is available on the market as a food supplement and registered as an active pharmaceutical ingredient. The structure of this compound is characterized by the presence of two chiral centers in positions 2 and 3 of the pyranone ring. Current regulatory documentation on DHQ lacks quantitative analysis of the stereoisomers of this flavanonol. This poses potential risks for consumers of DHQ-based dietary supplements and developers of new drugs. This review was conducted to systematize data on the pharmacology of DHQ stereoisomers and the possible methods of controlling them in promising chiral drugs. We found that relying on literature data of polarimetry for the identification of DHQ stereoisomers is currently impossible due to these heterogeneities. NMR spectroscopy allows to distinguishing between trans- and cis-DHQ using chemical shifts values. Only HPLC is currently characterized by sufficient enantioselectivity. Regarding pharmacology, the most active stereoisomer of DHQ should be identified, if the substituents in chiral centers both take part in binding with the biological target. The significant impact of stereochemical structure on the pharmacokinetics of DHQ isomers was reported. The question about these toxicity of these compounds remains open. The results of the conducted review of scientific literature indicate the necessity of revising the pharmacology of DHQ taking into account its stereoisomerism.